Genetic diversity of a European collection of loquat (Eriobotrya japonica (Thumb.) Lindl.) determined by molecular markers - Badenes M.L.; Canyamas T.; Romero C.; Soriano J.M.; Martínez J.; Llácer G. (First international symposium on loquat, 2003)
Loquat [Eriobotrya japonica (Thumb.) Lindl.] was introduced in Europe in the 18th century. At present, it is an interesting alternative for the European fruit industry. A germplasm collection from Spain and accessions introduced from Japan, Italy and Portugal was studied by means of RAPD markers. 34 highly reproducible markers were selected among 46 accessions. The polymorphism detected allowed us to distinguish 39 accessions. Our results suggested that, although a large number of new accessions were identified, the genetic diversity of loquat in Europe is very low. A few forms were introduced from Japan. The species was seed propagated and developed many budsport, the genetic base being narrow. To improve the identification of closely related accessions, eighteen sequences flanking microsatellites from Malus domestica L. were screened in a set of accessions. All sequences amplified SSR markers in the set of cultivars. According to these results, microsatellites are a useful alternative marker system for loquat genotyping.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)